Genetic Variation of Eight Indonesian Swamp-Buffalo Populations Based on Cytochrome b Gene Marker - M. Rusdin; D. D. Solihin; A. Gunawan; C. Talib; C. Sumantri (Tropical Animal Science Journal, 2020)
Genetic variation is a major concern in animal genetic resources conservation program. This study aimed to analyze genetic variation and phylogeography of eight Indonesian swamp-buffalo populations based on cytochrome b gene marker. A total of 78 DNA fragment samples originating from eight Indonesian swamp-buffalo populations were used in this study, namely Bombana Island, Bombana mainland, Kolaka, Konawe, North Toraja, West Nusa Tenggara, Banten, and Aceh with 11, 10, 13, 14, 10, 10, 5, and 5 samples, respectively. The cytochrome b gene sequence and genetic variation parameters were analyzed in MEGA software (ver 6), and DnaSP software (ver 5.10.01). The results of this study showed that all DNA-fragment samples were successfully amplified by PCR technique with the size target (906 bp). Based on the distribution of all samples, it was found 9 polymorphic sites, and 10 haplotypes with the haplotype diversities were 0.6590. The average of genetic distances between populations ranged from 0.0000-0.002. They were grouped into two main clusters. The first cluster consisted of Aceh, North Toraja, West Nusa Tenggara, Banten, Kolaka, and Konawe populations, meanwhile, the second cluster consisted of Bombana Island, Bombana mainland, Kolaka, and Konawe populations. The results of the study were concluded that eight Indonesian local swamp-buffalo populations were grouped into two main clusters where Bombana Island and Bombana mainland populations were specific breeds because they were only found in the second cluster and also had specific nucleotides sites on the 57 nucleotides which C base changed to T. The results of this study were useful in formulating the program of conservation and utilization of Indonesian buffalo genetic resources, especially in the buffalo population with specific breeds.